Acute effects of ballistic vs. passive static stretching involved in a prematch warm-up on vertical jump and linear sprint performance in soccer players - Mariscal, S. L.; Garcia, V. S.; Fernández-García, J. C.; de Villarreal, E. S. (The Journal of Strength and Conditioning Research, 2021)
The purpose of this study was to compare the effects of introducing passive static and ballistic stretching in a standard soccer match warm-up. The variables addressed were the counter movement jump (CMJ), Abalakov jump, and the 40-m linear sprint. The sample was composed of 33 male subjects, divided into 2 age groups. U16 and adult players formed the groups, to cross check whether there were differences between them. Each group was further subdivided into 2 groups regarding the type of stretching carried out during the stretching phase. Before the warm-up, the tests previously described were assessed. In the experimental phase, standard stretching was carried out, consisting of an initial phase in which players had to execute continuous running; a general phase in which players had to make articulate moves; a technical phase in which players had to execute exercises with the ball; a 5 vs. 5 small-sided game was carried out during the tactical phase; and in the final phase, activation exercises and sprints were carried out by the players. Eventually, the same variables were assessed again once the warm-up was finished. There were no statistically significant differences between the 2 types of stretching included in the prematch warm-up. It can be concluded that ballistic and passive static stretching (<10 seconds) did not cause, under these circumstances, any effect in the assessed variables related to soccer performance (linear sprint, CMJ, and Abalakov). This has to be considered by coaches when devising soccer-related warm-ups.